Diagnosis of spontaneous bacterial peritonitis in cirrhotic patients in northeastern Brazil by use of rapid urine-screening test - Braga, Lucia Libanez Bessa Campelo; Souza, Marcellus Henrique Loiola Ponte de; Barbosa, Alzira Maria de Castro; Furtado, Felipe Magalhães; Campelo, Paula Andréa Maia; Araújo Filho, Antônio Haroldo de (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: Spontaneous bacte- rial peritonitis (SBP) is a frequent and severe complication of cirrhotic patients with ascites. It has been proposed that the reagent strip for leukocyte esterase designed for the testing of urine (Combur test® UX) could be a useful tool for diagnosing SPB. The aim of this study was to assess the sensitivity and specificity of urine test strips for diagnosing SBP in cirrhotic patients with ascites. DESIGN AND SETTING: Prospective study, at a university hospital in northeastern Brazil. METHODS: Forty-two unselected consecutive cirrhotic patients (32 males; mean age: 51.7 ± years) were included, and a total of 100 para- centeses were performed. All ascitic fluid samples were analyzed using the reagent strip and cytol- ogy, neutrophils, lymphocyte count, appropriate biochemical tests and culturing. The strips were considered positive if the color became purple on a colorimetric scale. RESULTS: Nine patients were diagnosed with SBP using cytology (> 250 neutrophils/mm3), and the strips were positive for all these nine patients with SBP. In one sample, the strip was positive but the neutrophil count was less than 250 cells/mm3. For 86 samples, both the strips and cytology were negative. At the threshold of 250 neutrophils/mm3 in ascitic fluid, the sensitivity, specificity, positive predictive value and negative predictive value for the strips were respectively 100%, 98.9%, 92.3% and 100%. CONCLUSION: The Combur test® UX urine screening test is a very sensitive and specific method for diagnosing SBP in cirrhotic patients with ascites.